Sosialisasi Undang-Undang ITE Dalam Mempersiapkan Siswa SMK Cyber Media Memasuki Lingkungan Kampus - Herdiana, Dadan; Hadi, Abdul; Arifai, Mukhamad Khotib (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2019)
This activity is motivated by the number of young people who do not understand how to use social media properly and correctly, therefore it is necessary to socialize about the ethics of using the internet, especially social media among school-age children. Based on these problems, a counseling about the ITE Law and Preparation for Entering the Campus Environment were carried out at the Cyber Media Vocational School in Jakarta. This activity aims to provide understanding to Cyber Cyber Vocational students about the importance of ethics using internet media and social media. This activity also aims to provide an overview of the education system at the university in preparation for entering the campus environment. This activity is carried out by using counseling methods in the form of lectures accompanied by interactive discussions between participants and speakers. Based on the evaluation after the socialization of the ITE Law and the preparation to enter the campus environment, it was found that there was an increase in knowledge and very good understanding based on the results of the posttest conducted after the activity to the students of SMK Cyber Media. The conclusion was that the activity was successful and gave positive results to the understanding of students of Cyber Media Vocational School Jakarta on internet ethics. It is recommended that similar activities continue to be carried out so that more and more young people understand the ethics of using the internet, especially social media.